Indian Plant Recognition System Using Convolutional Neural Network - Naglot, Deepali; Kasliwal, Prachi Sandeep; Gaikwad, Swati Jayaji; Agrawal, Nisha Deepak (International Journal of Computer Sciences and Engineering, 2019)
Plants plays important role in our lives, as it provides us food and oxygen which is needed by all living things. There are thousands of kinds of trees in this world, and it is very difficult to distinguish between them. Experts can however identify by using characteristics of leaves but a common man cannot. Recognition of Plant from images is a challenging computer vision task. Proposed System is deployed to classify Indian local leaves automatically using deep learning. Deep Learning is a self-learning technique used for massive data and recent development in hardware and big data have turned out as a blessing. We have considered 10 different Indian plants leaves. Recognition rate of proposed system is 93%.